Colour Pattern as an Additional Aid to the Identification of Nemipterus Species and Their Relationship - Mohd Said, Mohd Zaki; Ambak, Mohd Azmi; Mohammad Mohsin, Abu Khair (1990)
Morphometric and meristic characters of six species of the genus emipterus collected from the South China Sea of Terengganu were found overlapping and differing only very slightly. But the colour pattern of live specimens seemed to differ greatly and on this basis a field key for their identification has been presented.